Rebels With a Cause : The Failure of the Left in Iran - Behrooz, Maziar (London I.B. Tauris Publishers, 2000)
This work unearths details and provides updated insights into an enduring puzzle of modern Iranian political history, concluding that the Left's demise came from a combination of Iran's geopolitical setting, as well as internal factors such as splits and factionalism
Include Note, Bibliography and Index
Keywords: Right and left (Political science) -- Iran -- Politics and government -- Communism